Os movimentos estudantis na História da Educação e a luta pela democratização da universidade brasileira - Marisa Bittar; Mariluce Bittar (EccoS – Revista Científica)
Although the field of research in History of Education has been continuously strengthened in recent decades and diversifying its sources and themes, the student movement, led by brazilian youth, is still not regarded as an object of study. So, with this article we intended to contribute to the knowledge of an aspect that sparked more interest in the past than today. In the first part, the article discusses the characteristics of the university since its appearance until the crisis of the 1960s, when the student riots erupted demanding democratic reforms in its structure. The second examines the contribution of brazilian student movements in the twentieth century to the democratization of brazilian university relating them to the moments of the struggle for democracy itself in the country. The article was based on bibliographic sources on the topic as well as documents from the National Union of Students (UNE) and the Brazilian Union of Secondary Students (UBES).